Secondary Prevention of Coronary Heart Disease in Primary Health Care - Olivera Batić-Mujanović; Muharem Zildžić; Azijada Beganlić (Biomolecules & Biomedicine, 2006)
Significant increase in mortality from coronary heart disease (CHD) has been seen in Bosnia and Herzegovina in the past decade. Little is known about current secondary preventive practices and treatments among patients with CHD in primary health care. The aims of this study were to evaluate the components of secondary prevention for CHD and to detect possible gender differences. This trial included 70 patients, aged 40-70 years, with established CHD from Family Medicine Teaching Center Tuzla. We evaluated components of secondary prevention(serum total cholesterol and blood pressure levels, smoking habits, body mass index, using aspirin, ACE inhibitors and lipid lowering drugs) in all participants. Results showed that significantly more men than women had diagnosis of CHD. 26/70 (37.14%) patients had myocardial infarction, with significantly higher number of men than women, but more women had angina only. Mean systolic blood pressure was 148.09+/-20.22 and diastolic 91.62+/-10.17 mmHg; mean total cholesterol level was 6.23+/-1.33 mmol/l; mean BMI was 27.9+/-3.32 kg/m(2). Blood pressure was managed according to guidelines in 19 (27.14%), and lipid concentrations in 11 (15.71%) patients. 55/70 (78.71%) patients took aspirin, only 18/70 (25.71%) patients took lipid lowering therapy, and 20/23 (86.96%) patients with heart failure took ACE inhibitors. 16/70 (22.86%) patients were current smokers, only 19/70 (27.14%) patients had healthy body mass index, while 21/70 (30%) patients were obese. Results of this study show a suboptimal secondary prevention in primary health care, which indicate more effective public health messages and changes in the healthcare system that promotes preventive strategies.